Caracterización de la Feria libre de Cariamanga, cantón Calvas, provincia de Loja, para el primer trimestre de 2018 - Correa Vivanco, Carlos Augusto. (2018)
The current project’s main goal is to know the reality of the merchants in the Local Market of Cariamanga, located in Calvas – province of Loja to characterized the social and economic conditions of the individuals who perform these activities. In order to reach this proposal, two steps were followed: the administration of a first survey to stablish the social conditions of the merchants and the application of a second survey to determine the economic circumstances of the dealers. Throughout this study, it was found that regarding the social conditions, adult women with a basic education predominant level are the main participants in merchandize exercises, which reflects the little interest in further academic preparation, and therefore, preferring agricultural activities upon education. Finally, concerning the economic circumstances, it was determined that the majority of the market participants consider themselves retail merchants, with an equivalent income level of 0-49 dollars per week, whether they are good or bad. To conclude, this project has demonstrated to be valid and transferable, becoming apt to be applied in the public administration field.